Distúrbios respiratórios e fatores epidemiológicos em crianças aos cinco anos de idade em Aracaju - SE - Bezerra, Thaysa Samanta (2015)
Respiratory diseases are considered a global public health problems, especially in developing countries where morbidity and mortality are higher. Epidemiological factors influencing maternal health especially during pregnancy and the environmental and socioeconomic conditions to which the minor is exposed are determinants of children´s respiratory health; however their interrelations still stimulate reflections. This study aimed to evaluate the prevalence of respiratory disorders and epidemiological factors and analyze their association in children at five years of age. The study sample consisted of cohort |Epidemiological Study-Social Health Perinatal Hospital Births of the Great Aracaju| in two different times that were collected in 2005 and 2010, with clinical examinations and questionnaires relating to risk factors for childhood respiratory health. Was held Descriptive, bivariate using Chi-square test and multivariate Poisson regression modified by robust standard errors. Data were considered statistically significant when p ≤ 0.05 value. 429 children were evaluated, 55% were male, with weight and length / height appropriate. The frequency of breastfeeding and exposure to secondhand smoke were 91% and 28%, respectively. Among the maternal variables found prior to pregnancy asthma (3%) and during pregnancy (6%), vaginal delivery (72%), mother´s age at birth (± 25 years), maternal education ≤ 8 years of study and situation work outside the home in both evaluations. Regarding socio-economic conditions found government support (31% in 2005 and 67% in 2010) and family income between 1-3 minimum wages in the two sample points. The environment was demonstrated airy bedroom (58%), shared with adults (43%), mold located on the fourth (16%) and equipment to cook without waste by 98%. The prevalence of infant respiratory disorders accounted for 58%, and respiratory infections (47%), respiratory allergies (24%) and asthma (10%). In multivariate analyzes presented protection for respiratory infection in children who share bedrooms with other higher risk for those who had continuous hoarseness and were delivered vaginally. The variables related to the risk of respiratory allergy were children who snore during sleep, has continued hoarseness and have no pets, while protection for disease was associated with maternal education ≤ 8 years of schooling in 2010 and practice of child physical activity. The risk for asthma was linked to shortness of breath and asthmatic relative (mother, father, brothers and others like uncles, cousins and grandparents) and protection when maternal education ≤ 8 years of study in 2010. This study developed in Aracaju- SE with children to 5 years of age and their mothers showed high prevalence of respiratory disorders, linked to the relevant factors to childhood, to maternal, socioeconomic and environmental conditions, so children need early diagnosis and approach to prevent chronic morbidities and consequently, changes in respiratory health.